Opioid consumption following foot and ankle surgery: a systematic review - DeMaio, Christian; Nayfa, Robert; Reasnor, Ty Reasnor; Fox, Jake; Burrow, Zackary; Thompson, Samuel; Amgad Haleem (Journal of the Foot & Ankle, 2024)
Objective: Systematically review studies characterizing postoperative opioid consumption in patients submitted to foot and ankle surgery to identify trends in opioid consumption among regions of procedures (forefoot, midfoot, hindfoot/ankle) and ultimately create prescribing guidelines that treat patient’s pain adequately while limiting leftover pills. Methods: A systematic review was performed following the Meta-analysis of Observational Studies in Epidemiology (MOOSE) guidelines. Retrospective and prospective observational cohort studies that reported mean opioid consumption following foot and ankle surgery were included, as well as data from our institution that fit the review’s parameters. Studies that did not report this data or reported patients receiving alternative surgical techniques were excluded. The risk of bias in non-randomized studies – of exposure (ROBINS-E) tool and the Methodological index for non-randomized studies (MINORS) criteria were used to assess bias and study quality, respectively. Results: Three hundred ninety-five articles were identified, and six studies, including our institution’s, met inclusion criteria. Reported data from 2,445 patients were synthesized to show opioid consumption overall, by region of surgery, and by invasiveness of procedure. Four of five studies found significantly higher opioid use postoperatively in patients submitted to hindfoot/ankle surgery, and two of five studies found significantly higher consumption among those submitted to bony foot and ankle surgery. Conclusion: Prescribing physicians must approach foot and ankle patients on a case-by-case basis to ensure adequate pain management while mitigating excess opioid risk. For prescriptions of 5 mg oxycodone pills, we recommend 15-, 20-, and 25-pill prescriptions for patients submitted to forefoot, midfoot, and hindfoot/ankle surgery. Level of Evidence I; Systematic review.